Navigating turbulence, sustaining growth (The World Bank (WB), 2011)
Growth in developing East Asia in the first half of 2011 remained strong, but continued to moderate, mainly due to weakening external demand. Global growth was also affected by supply shocks from geopolitical disturbances in the Middle East, supply chain disruptions following the earthquake and tsunami in Japan, and a slower-than-expected recovery of private demand in crisis-affected countries